Assessing the effect of educational intervention based on BASNEF model on promoting physical activity among postpartum women - Akram Mahboubi Rad; Azar Tol; Davod Shojaeizadeh; Mehdi Yaseri (Payesh, 2016)
Objective (s): Physical inactivity is one of the biggest public health concerns. Due to various reasons such as pregnancy, women are more at risk of physical inactivity. This study performed to determine the influence of an educational intervention on promoting postpartum physical activity based on BAZNEF model, among women referred to health centers. Methods: This was a quasi-experimental study which conducted on 168 women referred to health centers during six weeks to one year after delivery. Samples divided in two groups; intervention and control by using a random allocation. Data collected by BASNEF questionnaire and International Physical Activity Questionnaire(IPAQ).. The educational intervention was designed in four sessions. Control group received no intervention except postpartum routine care. Three months after intervention, the questionnaire was completed again in two groups. Results: Pretest results revealed no significant differences in demographic characteristics and BASNEF model constructs in both groups (p>0/05). However, after intervention there was a significant differences between two groups in terms of BASNEF model including knowledge, attitude, normative believes, enabling factors and intention (P<0.001). Women’s physical activity who were in moderate and vigorous levels, had a significant increase (P<0.001). Conclusion: The findings suggest that the educational intervention based on BASNEF model can improve postpartum physical activity.